Clinical profile of hyponatremia in critical care patients in a tertiary care centre in India - Prajakta Patil; Sukanya Dasgupta; Arundhati Diwan; Shivakumar Iyer (Critical Care Innovations, 2022)
INTRODUCTION: : Disorders of sodium and water metabolism are frequently encountered in patients admitted to the Intensive Care Unit (ICU), and may even be acquired there. A systematic approach is needed to evaluate the causes of hyponatremia for better patient care. MATERIAL AND METHODS: 100 adult patients with admission serum sodium levels <135 mEq/L in the ICU were recruited for this study over 18 months. Through history taking and appropriate laboratory investigations, the prevalence, causes, morbidity and mortality of hyponatremia were assessed. Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH) was diagnosed using Schwartz and Bartter clinical criterion. RESULTS: 23 cases were deemed to have pseudohyponatremia likely caused by dyslipidemia or hyperproteinemia, whereas remaining 77 cases had true hyponatremia. Values of arterial and venous sodium have a positive correlation indicating agreement between the parameters. Majority of subjects were males (61%). Causes of hyponatremia include: neurological causes in 34 cases (44.2%), followed by gastrointestinal cause 18 cases (23.4%), respiratory cause 15 cases (19.5%), cardiac cause 5 cases (6.5%), and other causes 5 cases (6.5%). Most frequently encountered diagnosis included cerebrovascular accident (16 cases), pneumonia (10 cases), metabolic encephalopathy (10 cases), acute gastroenteritis (8 cases) and tubercular meningitis (6 cases). Of 77 cases studied, 18 cases (23.4%) had hypovolemic hyponatremia (due to acute gastroenteritis), 51 cases (66.2%) had euvolemic hyponatremia (due to SIADH, likely caused by cerebrovascular accident, pneumonia or metabolic encephalopathy) and 8 cases (10.4%) had hypervolemic hyponatremia (due to chronic renal failure or congestive cardiac failure). Mortality in this population was 11.7%, and was seen mainly in patients of severe hyponatremia. CONCLUSIONS: Severity of hyponatremia, male gender and neurological symptoms correlated significantly with morbidity and mortality in this cohort and the information from this study can be used to better identify patients at risk of adverse outcomes due to hyponatremia in critical care setting.